Ectopic Undescended Parathyroid Adenoma—SPECT/CT Avoids False-Negative Interpretation on 99mTc-MIBI Dual-Phase Scintigraphy. (March 2018) - Mahajan, Sonia; Schoder, Heiko
Abstract : Abstract: Undescended parathyroid adenomas are rare, and they are easily missed during neck exploration surgery in patients with hyperparathyroidism. Few reports have described ectopic parathyroid adenomas along the carotid arteries at or near the carotid bifurcation. These may be missed on planar 99m Tc-MIBI dual-phase scintigraphy because of overlapping submandibular gland activity. Our case demonstrates the potential advantage of SPECT/CT in parathyroid scintigraphy to overcome this limitation.